Assessment of land use and slope influence on soil organic carbon stocks and soil properties in Southern Ethiopia - Wachu, Cherinet Miju; Ibrahim, Araba Jemal (Frontiers in Agronomy, 2025)
Understanding the impact of land use on soil organic carbon stocks (SOCS) and soil properties is crucial for effective soil management and mitigating climate change. This study aimed to evaluate the effects of land use and slope on SOCS and soil properties in Southern Ethiopia. Soil samples were collected from the upper, middle, and lower slopes, with a total of 54 composite samples representing different land uses. The result revealed that total nitrogen, potassium, and organic carbon in land use and slope position were significantly affected. The highest soil organic carbon stocks, total nitrogen, and organic carbon values were observed in the enset-based land-use system, which also recorded. In lower slope showed the lowest levels of organic carbon (3.27%), total nitrogen (0.28%), available phosphorus (3.58 ppm), and SOCS (73.38 mg ha−1). The results indicated that different land-use systems influence the soil’s physicochemical properties and the variation of slope varies in forestry and enset land use system results of the soil properties studied. Based on these studies forestry and enset land system tremendous potential raise soil fertility capacity and diminish loss of soil nutrient and more conservation minded. Therefore, we concluded that using different plant residual materials and mixed farming methods, such as agroforestry, promotes the sustainable maintenance of soil physicochemical properties for both the present and the future. This underscores the need for integrated land management to boost carbon storage, enhance soil fertility, and combat climate change.